Design Improvement of Laboratory Chair Used at Universiti Tun Hussein Onn Malaysia, Pagoh Campus Based on Ergonomic Factors - Ibrahim, Rafidah; Helmy Mustafa El Bakri (Progress in Engineering Application and Technology, 2022)
This study looks on laboratory seating designs that were based on ergonomic principles. Ergonomics is the study of fitting a product to its users or a job to its workers. Unfortunately, ergonomic considerations are not always taken into account while designing furniture. User characteristics such as body height, weight, and each portion of the body measurement must be taken into account while designing furniture. This research is being conducted at the Campus Pagoh of Universiti Tun Hussein Onn Malaysia. The main objective of this project was to improve the chair design in the laboratory. The project’s insistence came from users’ poor posture when using the laboratory’s seats which can lead to health issues such as back pain and spinal misalignment. The simulation analysis is done using SOLIDWORKS software and tested using static analysis and fatigue analysis. The result shown that the design can undergoes a force around more 1000N on its seat without being broken. Therefore, this design can achieve the objective stated. Kinovea software was implemented to measure the user’s posture in this study. The Rapid Body Assessment (REBA) tool was used to examine each measurement of various body part posture in order to determine the risk level of the laboratory’s chair.The existing laboratory seating received a REBA score of 8, indicating a high risk that requires investigate and implement change. This project also conducted a online survey, which revealed that 89% of respondents experienced difficulties using the laboratory’s seats. SOLIDWORKS software was applied to create a proposed design for laboratory chairs. The proposed design includes desirable characteristics such as an adjustable backrest lumbar support, and footring. The suggested seat design received a REBA score of 5, which is significantly lower than the current design’s REBA score. It was illustrating by Catia software to take the angle posture from the model so that the major differences in ergonomic factors between the current and proposed designs can be compared.